Counting the cost: Estimating the number of deaths among recently released prisoners in Australia - Kinner, S.; Preen, D.; Kariminia, A.; Butler, Tony; Andrews, J.; Stoové, M.; Law, M. (2011)
Objective: To estimate the number of deaths among people released from prison in Australia in the 2007-08 financial year, within 4 weeks and 1 year of release. Design, participants and setting: Application of crude mortality rates for ex-prisoners (obtained from two independent, state-based record-linkage studies [New South Wales and Western Australia]) to a national estimate of the number and characteristics of people released from prison in 2007-08. Main outcome measures: Estimated number of deaths among adults released from Australian prisons in 2007-08, within 4 weeks and 1 year of release, classified by age, sex, Indigenous status and cause of death. Results: It was estimated that among people released from prison in 2007-08, between 449 (95% CI, 380-527) and 472 (95% CI, 438-507) died within 1 year of release. Of these, between 68 (95% CI, 56-82) and 138 (95% CI, 101-183) died within 4 weeks of release. Most of these deaths were not drug-related. Conclusion: The estimated annual number of deaths among recently released prisoners in Australia is considerably greater than the annual number of deaths in custody, highlighting the extreme vulnerability of this population on return to the community. There is an urgent need to establish a national system for routine monitoring of ex-prisoner mortality and to continue the duty of care beyond the prison walls. © The Medical Journal of Australia 2011.